Rola i zadania prezbiterów we wspólnocie kościelnej w świetle pism Tertuliana - Zalewski, Dariusz (Vox Patrum, 2019)
Tertullian did not bequeath any treaty directly about Church and organization of it. Well, he certainly did not regard it as something required. The aggregate of his works quite precise shows how Church in North Africa functioned in II and III century. In his works term presbyter it seems to be ultimately stated. The term determines the second level of beadle, subordinate authority of supervisor of community – pontiff. For that reason, presbyters did not arouse our author, who frequently lists them in relation with the superior. They participated in actions appropriate for pontiff such as education or gave baptism to somebody. Moreover, they confirm Christian marriage and they achieve intercessory function while public expiation sinners. However, they probably do not possess power to absolve worshippers. Tertullian especially point out their disciplinary function, they had to provide peace in the community although they create with pontiff and deaconry the hierarchy in Church.